Corrigendum to “Mg-doped CoCr₂O₄ nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage” [Chem. Eng. J. 535 (2026) 175200] - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

Mg-doped CoCr2O4 nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

Spatio-temporal dynamics of fish assemblages at an offshore wind farm and a comparison with mature artificial reefs - Kwang Tsao Shao; Ching Han Chang; Ching Yi Chen; Lin Tai Ho; Yi Ta Shao; Hsin-Chieh Chiang; Wei-Ning Lee; Hsien Ju Tsai; Tien-Yu Huang; Chun-Yu Chang (Frontiers in Marine Science, 2026)
Introduction Offshore wind farms (OWFs) are vital for sustainable energy. The underwater foundations of those wind turbines provide a complex structure that creates new habitats and attracts fishes. However, whether OWFs had the same ecological function as purpose-built artificial reef (AR) and how they alter the original fish community remain unclear. Methods To evaluate the spatial and temporal variations in fish assemblages, we conducted a multi-part investigation at the Formosa Wind Farm, located off the coast of Miaoli County, Taiwan. Temporal changes were assessed through SCUBA surveys at turbine foundations in 2017, 2018, and 2025, with the 2025 data allowing for a direct comparison with the nearby existing artificial reefs. To assess spatial effects, pole-and-line surveys were conducted from Apr to Oct in 2024 and 2025 at varying distances from the turbines. Results Our investigation documented 86 species of reef-associated fishes exclusively within 50 m of turbine foundations; none were caught in the surrounding sandy areas or documented in pervious fishery records. The results demonstrated that fish assemblages around the turbine piles changed successively over the years. Although the species composition in 2025 differed between the OWF and the established AR sites, key ecological metrics such as species richness, diversity, and trophic structures showed no significant differences. Discussion These findings demonstrated that the underwater structure of offshore wind turbines can function as AR, creating novel reef habitats and supporting reef-associated fish community within a finite spatial extent. Overall, OWFs may provide ecological benefits in addition to renewable energy, highlighting their potential role in balancing energy development with marine conservation.

Trans-anethole enhances mesenchymal stem cell derived exosomes function to inhibit H2O2-induced rheumatoid arthritis-like inflammation in HIG-82 synovial cells - Tai-Lung Huang; Yu-Chun Chang; Wei-Wen Kuo; Shih-Wen Kao; Chia-Hua Kuo; Dennis Jine-Yuan Hsieh; Kuan-Ho Lin; Tsung-Jung Ho; Chih-Yang Huang (Molecular Biology Reports, 2025)

Energy cycle efficiency of the EU - Tai-Yu Lin; Yung-ho Chiu; Pai-Yun Hsiao (Environment, Development and Sustainability, 2025)

Alisertib inhibits acute myeloid leukemia cell growth by inhibiting STAT3 activation - Pang-Ting Cheng; Ho Lin; Yu-Chiao Cheng; Tzu-Hung Hsiao; Pei-Pei Jhan; Jia-Rung Tsai; Mei-Chih Chen; Tai-Lin Chen; Chieh-Lin Jerry Teng (Toxicology and Applied Pharmacology, 2025)

Evaluating European countries' progress towards SDGs: Insights from parallel SBM DEA analysis of economic, healthcare, environmental, and educational efficiencies - Tai-Yu Lin; Yung-Ho Chiu; Jia Sheng Lu; Liang-Chun Lu; Hsiu-Fang Chien (Journal of Environmental Management, 2025)

Linkage analysis for water-energy-economic system efficiency in China - Zhong Fang; Yung-ho Chiu; Yiqin Chen; Tai-Yu Lin; Tzu-Han Chang (Environment, Development and Sustainability, 2024)

Agricultural production efficiency, food consumption, and food waste in the European countries - Tai-Yu Lin; Shih-Yung Chiu; Yung-ho Chiu; Liang-Chun Lu; Kuei-Ying Huang (Environment, Development and Sustainability, 2023)

Profit-seeking enterprise production and business waste treatment efficiency in Taiwan - Tai-Yu Lin; Yung-Ho Chiu; Yi-Nuo Lin; Tzu-Han Chang (Environment, Development and Sustainability, 2023)

Dynamic total factors’ environmental efficiency in European union countries - Ching-Cheng Lu; Yung-ho Chiu; I-Fang Lin; Tai-Yu Lin (Environment, Development and Sustainability, 2023)

Analysis of natural disasters and energy efficiency in China - Zhong Fang; Yung-ho Chiu; Tai-Yu Lin; Tzu-Han Chang; Yi-Nuo Lin (Environment, Development and Sustainability, 2023)

Greenhouse gas emission indicators, energy consumption efficiency, and optimal carbon emission allowance allocation of the EU countries in 2030 - Tai-Yu Lin; Yung-Ho Chiu; Yi-Nuo Lin; Tzu-Han Chang; Pei-Yu Lin (Gas Science and Engineering, 2023)

Two-stage dynamic data envelopment analysis measuring the overall efficiency and productivity changes of industry and agriculture in EU countries - Ching-Cheng Lu; I-Fang Lin; Tai-Yu Lin; Yung-ho Chiu (Journal of Cleaner Production, 2023)

The influence of climate change on the allocation efficiency of new and tradition energy - Kuei-Ying Huang; Yung-ho Chiu; Tzu-Han Chang; Tai-Yu Lin (Environmental Science and Pollution Research, 2022)

Evaluating the energy, health efficiency, and productivity in OECD - Ching-Cheng Lu; Yung-ho Chiu; Chih-Yu Yang; Tai-Yu Lin (Environmental Geochemistry and Health, 2021)

Dynamic analysis of residential and enterprise water supply and leakage efficiencies - Ying Li; Yung-ho Chiu; Yushan Li; Hongyi Cen; Tai-Yu Lin (Environmental Science and Pollution Research, 2021)

Efficiency assessment of coal energy and non-coal energy under bound dynamic DDF DEA - Ying Li; Tai-Yu Lin; Yung-ho Chiu; Hongyi Cen; Yi-Nuo Lin (Environmental Science and Pollution Research, 2021)

Commonly Used Excipients Modulate UDP-Glucuronosyltransferase 2B7 Activity to Improve Nalbuphine Oral Bioavailability in Humans - Hong-Jaan Wang; Cheng-Huei Hsiong; Shung-Tai Ho; Min-Jen Lin; Tung-Yuan Shih; Pei-Wei Huang; Oliver Yoa-Pu Hu (Pharmaceutical Research, 2014)

Investigating the adaptation of muscle oxygenation to resistance training for elders and young men using near-infrared spectroscopy - Tai-You Lin; Linda L. Lin; Ting-Chuan Ho; Jia-Jin J. Chen (European Journal of Applied Physiology, 2014)

The enhancement of biofilm formation in Group B streptococcal isolates at vaginal pH - Yueh-Ren Ho; Chien-Ming Li; Chen-Hsiang Yu; Yuh-Jyh Lin; Ching-Ming Wu; I-Chen Harn; Ming-Jer Tang; Yi-Ting Chen; Fang-Chi Shen; Chien-Yi Lu; Tai-Chun Tsai; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2013)

Azo dye decolorization with a mutant Escherichia coli strain - Jo-Shu Chang; Tai-Shin Kuo; Yun-Peng Chao; Jin-Yen Ho; Ping-Jei Lin (Biotechnology Letters, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)